2014
DOI: 10.1177/0265532214538014
|View full text |Cite
|
Sign up to set email alerts
|

The extent to which TOEFL iBT speaking scores are associated with performance on oral language tasks and oral ability components for Japanese university students

Abstract: The purpose of this study was to determine the extent to which performance on the TOEFL iBT speaking section is associated with other indicators of Japanese university students’ abilities to communicate orally in an academic English environment and to determine which components of oral ability for these tasks are best assessed by TOEFL iBT. To achieve this aim, TOEFL iBT speaking scores were compared to performances on a group oral discussion, picture and graph description, and prepared oral presentation tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…These broad definitions of oral proficiency suggest that this ability includes: 1) interactional competence; 2) appropriate use of phonology; 3) appropriate and accurate use of vocabulary and grammar; and 4) appropriate fluency. (Ockey, Koyama, Setoguchi, and Sun 2015). Other research indicates that test takers prefer real-time tasks in which they actively co-construct meaning with other interlocutors.…”
Section: The Construct Of Oral Communicationmentioning
confidence: 99%
“…These broad definitions of oral proficiency suggest that this ability includes: 1) interactional competence; 2) appropriate use of phonology; 3) appropriate and accurate use of vocabulary and grammar; and 4) appropriate fluency. (Ockey, Koyama, Setoguchi, and Sun 2015). Other research indicates that test takers prefer real-time tasks in which they actively co-construct meaning with other interlocutors.…”
Section: The Construct Of Oral Communicationmentioning
confidence: 99%
“…In university settings, the TOEFL iBT, including the speaking component, has been adopted for both undergraduate‐ and graduate‐level decisions, as no strong evidence was found to support differences between academic levels and disciplines in terms of tasks relevant for course completion (Jamieson et al, ). Numerous studies validated such uses of the TOEFL iBT test with respect to various aspects of assessment, including test task design, relationships with other criteria in academic contexts, and factor structure (Bridgeman, Powers, Stone, & Mollaun, ; Ockey, Koyama, Setoguchi, & Sun, ; Sawaki, Stricker, & Oranje, ). A research agenda has also been initiated for ITA‐related uses of scores.…”
Section: Toefl Ibt Speaking and Domain Descriptionmentioning
confidence: 99%
“…Like the one-on-one oral interview, the reliability of paired/group oral tasks delivered by humans depends not only on the task type, but on the effectiveness of rater training. Research has shown that group test tasks can be moderately reliable (Bonk & Ockey, 2003;Ockey, Koyama, Setoguchi, & Sun, 2015), but, in part, because the discourse is controlled by the test takers, reliability is unlikely to be high.…”
Section: Assessment Delivery Options For Assessing Oral Communicationmentioning
confidence: 99%